O trabalho de mulheres transexuais e travestis no mercado do sexo - Jara, Marlon da Silva (2021)
The realities of transsexual women and transvestites in Brazil have been one of violence. For consecutive years, Brazil is the country that kills the most transsexual and transvestite women in the world. In this sense, the present study sought to understand how the bibliographic productions of Social Work in the last five years in Brazil have been constituted about transsexual women and transvestites who perform sex work in the sex market. Its general objective was to analyze the bibliographical productions about the work relationships of transsexual and transvestite women in the sex market in order to contribute with theoretical subsidies in the perspective of access to rights for this population segment. This is a bibliographical research that surveys the main productions carried out with this focus in the last five years. The research universe included studies carried out on transsexual women and transvestites who work in the sex market in Brazil. The survey of the works was carried out in the main magazines in the area of Social Work, such as Social Work and Society, Texts & Contexts and Katálysis, and also in the Capes Theses and Dissertations Catalog and in the Digital Library of Theses and Dissertations (BDTD). The following descriptors were used: women, transvestites; transsexuals; sex market for the selection of works that would compose the corpus of analysis. The sample consisted of a total of 12 productions, 2 theses, 8 dissertations and 2 articles. The analysis of the research data was carried out based on content analysis (Bardin, 1977), as this technique meets the dialectical-critical method, thus trying to get to know the complex aspects of bibliographies. We found that the bibliographic productions of Social Work have demonstrated the reality experienced by transsexual and transvestite women in Brazil, in which they have their experiences crossed by multiple expressions of the social issue. Prejudice, as one of these expressions of the social issue, is central to these experiences, as it is present from the first years of their lives, when they begin to question the gender that was assigned at birth, determining violence in the family and at school. This violence suffered in the family and at school triggers other types of violence such as homelessness, bullying and non-insertion in the formal labor market, and are potentiated by prejudice/transphobia. This makes sex work in the sex market one of the few alternatives to guarantee their livelihood. Sex work in the sex market exposes transsexual women and transvestites to other forms of violence such as the financing of bodily adjustments by pimps and cafetinas, triggering bonded relationships, determining their indebtedness and increasing their exploitation in the work they perform. The bourgeois ideology, by prescribing ideal models of men and women determined by the genital, reproduces transphobia, making transsexual women and transvestites more vulnerable to physical and psychological violence in the sex market.